RELIABILITY ASSESSMENT OF THE SUCKER ROD PUMPING UNIT EQUIPMENT AND DEVELOPMENT OF OPTIMUM PLANS-GRAPHICS OF ITS REPAIR - Лопатін, Валерій Володимирович; Копей, Богдан Володимирович; Копей, Ігор Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Maintenance of equipment is possible at known values of work of components to failure or between failures. The task of choosing the value of work is complicated by the fact that the distribution of failures in time is probabilistic. There is the most expedient, optimal value of the work, in which the amount of expenses on the one hand due to the downtime of objects and on the other - due to underutilization of the resource parts and the increase in the number of repairs will be minimal. Method of finding the optimal recovery period for the equipment is proposed in the work and allows more accurately determining the life of the oil and gas equipment and developing a rational strategy for their maintenance and repair.